The determinants of bank regulations and supervision on the efficiency of Islamic Banks in MENA regions* - Mohd Noor, Nor Halida Haziaton; Bakri, Mohammed Hariri; Wan Yusof, Wan Yusrol Rizal; Mohd Noor, Nor Raihana Asmar; Abdullah, Hasni (Korea Distribution Science Association (KODISA), 2020)
This study investigates the impact of the country’s governance on the revenue efficiency in the banking sectors of 42 Islamic banks in 15 countries offering Islamic banking and financial services. Technical efficiencies of individual Islamic banks were analyzed using the Data Envelopment Analysis method. The Ordinary Least Square estimation method is employed to examine the impact of country supervision and regulation on the technical efficiency of Islamic banks. With robustness check, the study assesses the impact of bank regulations and supervision on the efficiency of Islamic banks operating in different regions. The empirical findings suggest that supervisory power, activity restrictions, and private monitoring positively influence the efficiency of Islamic banks. On the other hand, we observe a negative impact of capital requirement on Middle East and North Africa (MENA) countries. The findings indicate that supervisory power, activity restrictions, and private monitoring positively influence the efficiency of Islamic banks in Asia, but vice versa on capital requirement in MENA countries. This study will contribute to the body of knowledge by assessing the types of reforms in bank regulations and supervision that work best for Islamic banks in order to increase the level of efficiency and the level of regulations and supervision of Islamic banks.